PEMANFAATAN BAHASA ALAMI SEBAGAI ANTAR MUKA APLIKASI NL-FARAID - Setiaji, Bayu; Utami, Emma; Al Fatta, Hanif (Jurnal Teknologi Informasi RESPATI, 2012)
Patrimony science or faraid is a branch of science in Islamic law that discusses the ins and outs of the division of the estate based on descent in the family hierarchy. All the rules of calculation derived from the Qur'an and are discussed in the book devoted to the science of inheritance. It’s now widely available software that can be used as a tool for the calculation of the distribution of the estate so that it can be used by a layman though. The software is currently still used as a form-like based interface.Natural Language Processing or NLP is a branch of Artificial Intelligence or AI that allows the computers to understand natural language similar to those used by humans. While still on the use of written language, NLP has allowed the interaction between humans and computers can be done with natural language, no longer use the mediation form or the like. With the use of NLP can be made an heir by the name of counter application NL-Faraid (Natural-languaged Faraid) using natural language as a medium of inter-face.The results showed this application can be used to calculate the distribution of the estate. Applications can accept input and produce output calculations in the Indonesian language. Keywords: natural language processing, natural language, Indonesian language, faraid